A Conversational Implicature Analysis on the Split Movie - Belinda Mahira Putriayu; Ernie D. A. Imperiani (Universitas Pendidikan Indonesia (UPI), 2022)
Every conversation made between two parties or more must have arisen from specific contextual matters. Effort has become the case in achieving the wanted contextual rationality from the carried-out conversation which is connected to people’s strong will in creating ways to overcome the problem. In many attempts, movies, as a visual communication tool, have been used many times as a depiction of how real-life conversations are performed. Hence, this study which uses a descriptive qualitative method aims to investigate the use of maxim violation, maxim opt out, the types of conversational implicature, and their meaning of occurrence in the Split (2016) movie. To analyze the data, Grice’s (1975) theory on Conversational Implicatures and Yule’s (1996) theory on Cooperation and Implicature were used as the main theoretical frameworks. The data were taken from the movie script downloaded from the Scripts.com website while the movie was downloaded from the streaming-service platform, YouTube Movies. This study discovered that the violation of the maxim of manner, opt out of the maxim of quantity and quality, and particularized conversational implicature to be the mostly used ones in the conversations of the Split movie’s characters. The high occurrence of those implicatures demonstrates its purpose which is to make meaning of the characterization of the characters as their personalities and intentions are revealed. In line with the psychological feature that the movie as the data has, the findings also participate in the idea of people’s capability in interpreting the characteristic of others to be easily done.